Comparison of Manual and Semi-Automatic [18F]PSMA-1007 PET Based Contouring Techniques for Intraprostatic Tumor Delineation in Patients With Primary Prostate Cancer and Validation With Histopathology as Standard of Reference - Spohn, Simon K. B.; Kramer, Maria; Kiefer, Selina; Bronsert, Peter; Sigle, August; Schultze-Seemann, Wolfgang; Jilg, Cordula A.; Sprave, Tanja; Ceci, Lara; Fassbender, Thomas F.; Nicolay, Nils H.; Ruf, Juri; et al. (Frontiers in Oncology, 2020)
Purpose: Accurate contouring of intraprostatic gross tumour volume (GTV) is pivotal for successful delivery of focal therapies and for biopsy guidance in patients with primary prostate cancer (PCa). Contouring of GTVs, using 18-Fluor labelled tracer prostate specific membrane antigen positron emission tomography ([18F]PSMA-1007/PET) has not been examined yet. Patients and Methods: 10 Patients with primary PCa who underwent [18F]PSMA-1007 PET followed by radical prostatectomy were prospectively enrolled. Coregistered histopathological gross tumour volume (GTV-Histo) was used as standard of reference. PSMA-PET images were contoured on two ways: (1) manual contouring with PET scaling SUVmin-max: 0-10 was performed by three teams with different levels of experience. Team 1 repeated contouring at a different time point, resulting in n=4 manual contours. (2) Semi-automatic contouring approaches using SUVmax thresholds of 20-50% were performed. Interobserver agreement was assessed for manual contouring by calculating the Dice Similarity Coefficient (DSC) and for all approaches sensitivity, specificity were calculated by dividing the prostate in each CT slice into 4 equal quadrants under consideration of histopathology as standard of reference. Results: Manual contouring yielded an excellent interobserver agreement with a median DSC of 0.90 (range 0.87 – 0.94). Volumes derived from scaling SUVmin-max 0-10 showed no statistically significant difference from GTV-Histo and high sensitivities (median 87%, range 84-90%) and specificities (median 96%, range 96-100%). GTVs using semi-automatic segmentation applying a threshold of 20-40% of SUVmax showed no significant difference in absolute volumes to GTV-Histo, GTV-SUV50% was significantly smaller. Best performing semi-automatic contour (GTV-SUV20%) achieved high sensitivity (median 93%) and specificity (median 96%). There was no statistically significant difference to SUVmin-max 0-10. Conclusion Manual contouring with PET scaling SUVmin-max 0-10 and semiautomatic contouring applying a threshold of 20% of SUVmax achieved high sensitivities and very high specificities and are recommended for [18F]PSMA-1007 PET based focal therapy approaches. Providing high specificities, semi-automatic approaches applying thresholds of 30-40% of SUVmax are recommend for biopsy guidance.